PENGARUH DIGITAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN MENGINAP (Studi Pada OTA) - Putu Satcitanandadewi; Putu Indah Rahmawati; Trianasari Trianasari (Master of Management, Mataram University, 2023)
This research activity has a goal, namely to find out the effect of digital marketing variable aspects and electronic word of mouth variable aspects on the decision to stay. The researchers carried out the data collection process by usingThis research activity has a goal, namely to find out the effect of digital marketing variable aspects and electronic word of mouth variable aspects on the decision to stay. The researchers carried out the data collection process by using a questionnaire. The researchers have used the population, namely consumers (guests) whose age has reached 18 years and over. In carrying out the sample calculation process, a formula called Lemeshow will be used. The analysis technique used in this case is multiple linear regression and previously carried out the instrument testing process and the classical assumption testing process with the aim of knowing the accuracy of the results obtained with the help of support from the SPSS version 26.0 for windows program. The results of research activities show that (1) the variable aspects of digital marketing and electronic word of mouth variables simultaneously influence the decision to stay (2) the variable aspects of digital marketing show a positive and significant effect on the decision to stay and (3) The variable aspect of electronic word of mouth shows a positive and significant value influence on the decision to stay. Keywords: Digital Marketing, Electronic Word of Mouth, Stay Decision